PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBASIS BLENDED LEARNING DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Ni Komang Susmariani; I Wayan Widana; I Nyoman Rasmen Adi (Jurnal Ilmiah Pendidikan Citra Bakti, 2022)
This study aims to determine the effect of the guided inquiry learning model based on blended learning and independent learning on the mathematics learning outcomes of fifth grade elementary school students. The research sample was selected by random sampling technique totaling 68 people from 6 schools consisting of 3 experimental classes and 3 control classes. The research design is treatment by level with the test instruments for learning mathematics outcomes and learning independence questionnaires. The learning outcomes data in this study were analyzed using two-way ANOVA, then continued with the Tukey test. All tests were carried out at a significance level of 0.05. The results showed that (1) there were differences in the mathematics learning outcomes of elementary school students who followed the guided inquiry learning model based on blended learning with students who followed the conventional learning model (Sig < 0.05 or 0.017 < 0.05) ; (2) There is an interaction effect between the application of the learning model and independent learning on the mathematics learning outcomes of elementary school students. (Sig < 0.05 or 0.000 < 0.05); (3) There are differences in mathematics learning outcomes between students who follow the guided inquiry learning model based on blended learning and students who follow the conventional learning model in elementary school students who have high learning independence. (Qcount > Qtable or 10.0134 > 2.98); and (4) there are differences in learning outcomes of mathematics between students who follow the guided inquiry learning model based on blended learning and students who follow the conventional learning model in elementary school students who have low learning independence (Qcount > Qtable or 5.1329 > 2.98).